Design thinking teams and team innovation performance - Frode Heldal (Journal of Innovation and Entrepreneurship, 2023)
Design thinking (DT) is hailed as a cornerstone of innovation. It is based on teamwork, yet we know little about how the DT team operates and collaborates. In this study, we investigate 51 Norwegian master's student teams as they work on an innovation project using DT. We seek especially to understand how they communicate and collaborate while working with DT tools, with special attention to divergent and convergent thinking. Using a mixed methods approach, we analyze the teams' behaviors and developments in these. Findings suggest that the highest performing groups use the DT method with greater discipline than the other groups. To achieve this, they employ more authority-based behaviors and fewer supportive behaviors than the other groups. This disciplined approach to DT as a process and the use of tools, such as brainstorming, are in turn associated with convergent and divergent thinking. The main conclusions are that a disciplined approach using DT as a team tool, enables team reflexivity and psychological safety. This enhances innovative performance.
Keywords: 650; Convergent/divergent thinking; Design thinking; Innovation; Psychological safety; Team performance